2016
DOI: 10.1186/s13054-016-1569-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between time of discharge from ICU and hospital mortality: a systematic review and meta-analysis

Abstract: BackgroundEpidemiological studies have provided inconsistent results on whether intensive care unit (ICU) discharge at night and on weekends is associated with an increased risk of mortality. This systematic review and meta-analysis aimed to determine whether ICU discharge time was associated with hospital mortality.MethodsThe PubMed, Embase, and Scopus databases were searched to identify cohort studies that investigated the effects of discharge from the ICU on weekends and at night on hospital mortality, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
50
1
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 49 publications
5
50
1
4
Order By: Relevance
“…The inclusion of readmission as an outcome in the current study is important, because it may be a marker of deterioration after discharge. The previous review and meta-analysis by Yang et al included 14 observational cohort studies of 953,312 patients [1]. Their finding of increased mortality by 33% in out-of-hours discharge compared with in-hours discharge is compatible with the current meta-analysis.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…The inclusion of readmission as an outcome in the current study is important, because it may be a marker of deterioration after discharge. The previous review and meta-analysis by Yang et al included 14 observational cohort studies of 953,312 patients [1]. Their finding of increased mortality by 33% in out-of-hours discharge compared with in-hours discharge is compatible with the current meta-analysis.…”
supporting
confidence: 79%
“…The findings by Vollam et al extend results from a previous review and meta-analysis on time of discharge from ICU and mortality by including studies with and without adjustment for severity of illness and by including ICU readmission as an outcome [1]. The inclusion of readmission as an outcome in the current study is important, because it may be a marker of deterioration after discharge.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Several studies showed a relationship between daytime and weekday of discharge from ICU and outcome. They confirmed that unplanned discharges from the ICU during night-time and on weekends were independent risk factors for readmission to the ICU and increased mortality (18,23,24). Others confirmed high age, severity of illness on the day of admission to the ICU and day of discharge from the ICU as well as comorbidities as independent risk factors (8,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 90%
“…Several studies showed a relationship between daytime and weekday of discharge from ICU and outcome. They con rmed that unplanned discharges from the ICU during night-time and on weekends were independent risk factors for readmission to the ICU and increased mortality (18,23,24). Others con rmed older age, severity of illness on the day of admission to the ICU and day of discharge from the ICU as well as comorbidities as independent risk factors (8,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%